2010
DOI: 10.1007/s10640-010-9367-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Induced Value and Home-Grown Value Experiments to Test for Hypothetical Bias in Contingent Valuation

Abstract: This study tests the hypothesis that hypothetical bias may not be related to value elicitation; rather it may be a value formation problem. When participants are asked to indicate their willingness to pay for an induced value good, we find no evidence of hypothetical bias for three different commodity types (public good, private good, and publicly provided private good). However, when these same subjects are asked to value homegrown goods with no pre-assigned induced value using the same elicitation mechanism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
(47 reference statements)
3
24
0
Order By: Relevance
“…Among them, either the PC or MBDC format, which presents all of possible WTA values to respondents, would produce an unnecessary hypothetical bias due to the fact that people always have an incentive to choose a value that is more than he or she actually accepts [28,55]. With respect to the OE format, respondents should have the ability to estimate services or goods they provided, otherwise they have to leave the question blank or provide inaccurate answers resulting in information bias [56].…”
Section: Elicitation Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, either the PC or MBDC format, which presents all of possible WTA values to respondents, would produce an unnecessary hypothetical bias due to the fact that people always have an incentive to choose a value that is more than he or she actually accepts [28,55]. With respect to the OE format, respondents should have the ability to estimate services or goods they provided, otherwise they have to leave the question blank or provide inaccurate answers resulting in information bias [56].…”
Section: Elicitation Formatmentioning
confidence: 99%
“…As mentioned above, there are likely to be disparities or so-called hypothetical bias between eliciting and real WTA [55]. In order to minimize the bias and to fully simulate the real market, the study team conducted a pre-survey of 30 households in the area and talked with stakeholder-focus groups (e.g., government officials, village head).…”
Section: Measures Of Bias Controlmentioning
confidence: 99%
“…The related method of contingent valuation has been severely criticized based on these arguments (Carson et al 1996;Hausman 2012). However, a number of methods for reducing this bias have been suggested in the literature (List 2001;Murphy et al 2005;Carson 2012;Kling et al 2012), and several recent studies show that stated and revealed preferences often coincide (Murphy et al 2010;Jacquemet et al 2011). The results in these studies suggest that the importance of hypothetical bias depends on the experimental setting (Taylor et al 2001); the hypothetical valuation of a good is likely to exceed its actual valuation in situations which involve an important perceived ethical dimension and where a high value is considered 'ethically commendable', but not in other situations (Ajzen et al 2004;Guzman and Kolstad 2007).…”
Section: Validitymentioning
confidence: 99%
“…are chosen from a price list (Vossler and McKee, 2006;Murphy et al, 2010), although the use of a coarse grid of possible valuations does not provide narrowly-defined valuation estimates and thus a relatively weak test. Some studies have "trained" subjects on its revelation incentives using objects of known, objective value before using it to value things of interest (e.g., lotteries, products), e.g., Noussair et al (2004a;2004b).…”
Section: Figure 2: Decision Form Used In Both Roundsmentioning
confidence: 99%